Antimicrobial activities of novel class of dispirooxindolopyrrolidine grafted indanedione hybrid heterocycles against carbapenemase producing Klebsiella pneumoniae (CKP) - Shatha Ibrahim Alaqeel; Abdulrahman I. Almansour; Natarajan Arumugam; Raju Suresh Kumar; Karuppiah Ponmurugan; Naif Abdullah Al-Dhabi (Elsevier, 2021)
Background: Aggressive antimicrobial infections together with an increasing in resistance to antimicrobial medications cause a threat to immunocompromised individual. In this context, spiro compounds play an important role in drug discovery research due to their diverse biological activities including antimicrobial activity which is well documented in literature, because of their unique structural properties allow for easy interaction with the target enzyme of the biological system. This biological precedent encouraged us to design and synthesis of novel dispirooxindolopyrrolidine hybrid heterocycles via multicomponent cycloaddition protocol. Materials and methods: Novel class of dispirooxindolopyrrolidine hybrid heterocycles has been synthesized by multicomponent 1,3-dipolar cycloaddition methodology and the structure of the products was determined through spectroscopic analysis. The synthesized organic compounds were evaluated for their antimicrobial activities using sensitivity test with standard agar well diffusion method. Results: The synthesized new class of dispiropyrrolidine embedded indandione hybrids showed significant antimicrobial activity against carbapenemase producing Klebsiella pneumoniae (CKPs) isolated from hospital patients. Compound that possessing chlorine substituted on the aryl ring exhibited more potent antimicrobial activities and the zone of inhibitions was observed between 7.00 ± 0.09 and 18.40 ± 0.70 mm. The MIC value of compound 4b was 0.030 mg/mL against tested CKP. Conclusion: A new class of dispiropyrrolidine heterocyclic hybrids were synthesized in good to excellent yield employing multicomponent 1,3-dipolar cycloaddition strategy. Among them, compounds bearing 4-chloro substituted on the aryl ring exhibited notable activity just equal to the standard drug, ciprofloxacin. Future studies are needed to elucidate the pharmacological properties of new compounds that were synthesized in our laboratory for the novel therapeutic development.